2023
DOI: 10.1021/acsenergylett.2c02599
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activity of Defect-Engineered Transition Me tal Dichalcogenides Mapped with Atomic-Scale Precision by Electrochemical Scanning Tunneling Microscopy

Abstract: Unraveling structure–activity relationships is a key objective of catalysis. Unfortunately, the intrinsic complexity and structural heterogeneity of materials stand in the way of this goal, mainly because the activity measurements are area-averaged and therefore contain information coming from different surface sites. This limitation can be surpassed by the analysis of the noise in the current of electrochemical scanning tunneling microscopy (EC-STM). Herein, we apply this strategy to investigate the catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 76 publications
(162 reference statements)
0
11
0
Order By: Relevance
“…Subsequently, we show the nanosheets' nature of active sites using electrochemical noise scanning tunneling microscopy (n‐EC‐STM), [ 32 ] which enables an in situ observation of the local activity [ 33–36 ] as recently demonstrated by different groups. [ 37–39 ] These observations are supported and systematically explained by the most probable reaction pathways using density functional theory (DFT) calculations. Herein, the MnO 2 NS were modeled as a sheet of birnissite‐type δ‐MnO 2, which has been shown to have similar features to the Mn 4 CaO 5 in PS II.…”
Section: Introductionmentioning
confidence: 73%
“…Subsequently, we show the nanosheets' nature of active sites using electrochemical noise scanning tunneling microscopy (n‐EC‐STM), [ 32 ] which enables an in situ observation of the local activity [ 33–36 ] as recently demonstrated by different groups. [ 37–39 ] These observations are supported and systematically explained by the most probable reaction pathways using density functional theory (DFT) calculations. Herein, the MnO 2 NS were modeled as a sheet of birnissite‐type δ‐MnO 2, which has been shown to have similar features to the Mn 4 CaO 5 in PS II.…”
Section: Introductionmentioning
confidence: 73%
“…83,84 More recently, note that MoSe 2 monolayer (ML) grown by molecular beam epitaxy (MBE) on a bilayer of graphene (G) supported on a 6H-SiC single crystal (MoSe 2 /G/SiC) was used as a characteristic HER catalyst to individually detect the catalytic activity of the MoSe 2 basal plane, selenium vacancies, and different point defects produced by the intersections of metallic twin boundaries characterized using electrochemical scanning tunneling microscopy (EC-STM). 134 As is known, although MoSe 2 indicated a low electrical conductivity and a limited active site for HER performance, the conductivity of MoSe 2 is higher than that of MoS 2 owing to the substitution of highly conductive Se atoms (≈1 × 10 −3 S m −1 ) with low-conductive S atoms (≈5 × 10 −28 S m −1 ). Hence, MoSe 2 still showed relatively superior electrochemical catalytic activity and chemical stability.…”
Section: Single or Nonmetal Doped Mose 2 For Hermentioning
confidence: 94%
“…83,84 More recently, note that MoSe 2 monolayer (ML) grown by molecular beam epitaxy (MBE) on a bilayer of graphene (G) supported on a 6H-SiC single crystal (MoSe 2 /G/SiC) was used as a characteristic HER catalyst to individually detect the catalytic activity of the MoSe 2 basal plane, selenium vacancies, and different point defects produced by the intersections of metallic twin boundaries characterized using electrochemical scanning tunneling microscopy (EC-STM). 134…”
Section: Mose2-based Inorganic Composite For Hermentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we extend the investigations into the negative potential regime below the iodine adsorption/desorption peaks, where the TTMAPP molecules adsorb directly on the I-free (1 × 1) Au(100) surface . The use of both STM and CV in EC investigations in liquids enables the simultaneous in situ and in operando characterization of both the clean and the adsorbate-covered electrode surfaces. As specified above, by exploring the self-assembly of TTMAPP on an iodine-modified Au(100) electrode, this study aims to enhance our understanding of the potential-induced modification of noncovalent interactions, such as van der Waals and electrostatic forces, between the assembled molecules and the substrate. In this context, we also found that the adsorbed TTMAPP molecules not only hinder the readsorption of iodine on the surface but also hinder the desorption of iodine from the surface.…”
Section: Introductionmentioning
confidence: 96%